Determination of volatile organic compounds in the dried leaves of Salvia species by solid-phase microextraction coupled to gas chromatography mass spectrometry*. Issue 7 (2nd April 2016) - Cozzolino, Rosaria; Ramezani, Sadrollah; Martignetti, Antonella; Mari, Angela; Piacente, Sonia; De Giulio, Beatrice
Abstract: Salvia spp. are used throughout the world both for food and pharmaceutical purposes. In this study, a method involving headspace solid-phase microextraction combined with gas chromatography–mass spectrometry was developed, to establish the volatiles profile of dried leaves of four Iranian Salvia spp.: Salvia officinalis L., Salvia leriifolia Benth, Salvia macrosiphon Boiss. and two ecotypes of Salvia reuterana Boiss. A total of 95 volatiles were identified from the dried leaves of the five selected samples. Specifically, α-thujone was the main component of S. officinalis L. and S . macrosiphon Boiss. (34.40 and 17.84%, respectively) dried leaves, S . leriifolia Benth was dominated by β-pinene (27.03%), whereas α-terpinene was the major constituent of the two ecotypes of S . reuterana Boiss. (21.67 and 13.84%, respectively). These results suggested that the proposed method can be considered as a reliable technique for isolating volatiles from aromatic plants, and for plant differentiation based on the volatile metabolomic profile. Graphical abstract: